Study, Design, Modeling, Simulation, and Control Analysis of Single-Phase Rectifier AC-DC Power Converters - Salam Waley Shneen (Journal of Fuzzy Systems and Control, 2026)
Many researchers are interested in studying and analyzing electronic power systems due to their importance in providing the electrical quantities needed to meet load requirements. It's worth noting that there are different types of power sources, including direct current (DC) sources such as DC generators, batteries, or solar power, and alternating current (AC) sources such as diesel generators, wind power, and the main grid. Loads vary in that they require DC power, such as lighting, electric motors, and electronic devices. The most widely available power systems are single-phase AC systems, which can power loads of the same type. However, when DC loads, such as electric motors, are present, a rectifier is required to convert the DC current to AC. A rectifier consists of semiconductors such as diodes, thyristors, and transistors, and its output can be controlled by adjusting the operating period of the switches. This study aims to explore the differences between a single-phase half-wave rectifier and a full-wave rectifier. It presents a simulation model of a single-phase rectifier to conduct proposed tests to understand the system's behavior and analyze the simulation results to verify the rectifier's effectiveness in converting alternating current (AC) voltage to direct current (DC) voltage. The results confirm the convertibility capability, making the rectifier one of the important converters that can be used to supply DC loads with electrical power.